Customersa Perception of Service Quality of Islamic Bank in Bangladesh: An Empirical Analysis of Shahjalal Islami Bank Limited (Global Journal of Management and Business Research, 2015)
After Indonesia and Pakistan, Bangladesh is considered to be the third large Muslim populated country. The banking consumers now prefer Islamic Banking to conventional banking. In order to fulfil the higher demand of products and services of Islamic banking requires not only superior quality service but also prompt response to customer. In addition economical in operating system, strict compliance to Islamic Shari`ah and satisfactory community service through job creation and guaranteeing consistency in service provisions are also required. The study finds that consumers in Bangladesh really interested in Islamic banking and alongside they want superior customer value and satisfaction. SERVQUAL perception is fully used to find the service quality of Islamic banking in Bangladesh and also followed the five important instruments to identify the customers' observation of Shari`ah banking.
Keywords: islamic banking; service quality; customer perception